Wet deposition of ammonium, nitrate and non-sea-salt sulphate in Sweden 1955 through 2017. (April 2019) - Ferm, M.; Granat, L.; Engardt, M.; Pihl Karlsson, G.; Danielsson, H.; Karlsson, P.E.; Hansen, K.
Abstract: Wet deposition to Sweden has been measured on a monthly basis since 1955. Data from all national and international precipitation chemistry networks operating in Sweden during 1955–2017 was collected in one unique database. During 1990–2000, 146 sites were operated on average and the spatial distribution of deposition across Sweden was determined. The measurement sites were divided into three regions representing southwestern, southeastern and northern Sweden. The three regions clearly differ in deposition amount while the temporal variations were similar between the regions. Non-sea-salt sulphate (nss-SO4 2- ) wet deposition reached a maximum around 1970 and ammonium (NH4 + ) and nitrate (NO3 − ) in the mid-1980s. There was a reasonable agreement between the decreasing wet deposition trends of NH4 + and nss-SO4 2-, during 1990–2016 and the estimated decrease in the emissions in Sweden and Europe. The decreasing wet deposition trend of NO3 − was, however, weaker than the corresponding estimated reduction in emissions of NOx . The wet depositions of NH4 + and NO3 − were similar in magnitude during the whole measurement period and distributed in a similar manner between the three regions despite that these pollutants are transported over long distances and that the sources and atmospheric chemistry for NHx and NOx are different. Highlights: Historical and modern precipitation chemistry has been harmonized in a unique data set. Wet deposition of non-sea-salt sulphate to Sweden peaked around 1970. Wet deposition of ammonium and nitrate peaked in the mid-1980s. Sulphate wet deposition is now lower than in 1995; nitrogen wet deposition is higher. Trends and variability of wet deposition of ammonium and nitrate are similar.